Poly Î² Hydroxybutyrate Intriguing Biopolymer in Biomedical Applications and Pharma Formulation Trends - Jirage, Akshay S (International Journal of Pharmaceutical & Biological Archive, 2014)
Poly Î² Hydroxybutyrate Intriguing Biopolymer in Biomedical Applications and Pharma Formulation Trends